PERAN BUDAYA ORGANISASI DAN PEMBINAAN TERHADAP KINERJA PEGAWAI PADA BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN MUARA ENIM - Ismadi (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study was to determine and analyze the role of organizational culture and coaching on employee performance at the National and Political Unity Agency of Muara Enim Regency. Organizational Culture on the performance of the National and Political Unity Agency of Muara Enim Regency, Guidance on the performance of the National and Political Unity Agency of Muara Enim Regency, Organizational Culture and Guidance on the performance of the National and Political Unity Agency of Muara Enim Regency. In this study used primary data and secondary data, primary data obtained by distributing 2questionnaires to 22 respondents who became the sample. The data analysis technique used is Multiple Linear Regression from the SPSS software package, used in hypothesis testing. From the results of data analysis on the variables studied, namely leadership, education, motivation and discipline, it shows a significant relationship with employee performance at the National and Political Unity Agency of Muara Enim Regency.